Pulmonary hypertension associated with left heart disease: efforts to improve the meaning of haemodynamic phenotypes. Issue 3 (7th March 2019) - Gerges, Christian; Gerges, Mario; Lang, Irene M.
We appreciate the thoughtful comments of J.C. Grignola and colleagues in their letter addressing our article [1]. First, we agree that pulmonary hypertension associated with left heart disease (PH-LHD) is associated with global pulmonary vascular remodelling involving pulmonary arteries, veins and capillaries, as recently reported by Fayyaz et al . [2]. In fact, we have previously observed increased wall thickness and intimal fibrosis of small pulmonary arteries, even in patients with isolated post-capillary pulmonary hypertension (Ipc-PH) or "passive" pulmonary hypertension (PH) [3]. However, significant pre-capillary pulmonary vascular disease appeared to only be present in patients with combined post and pre-capillary PH (Cpc-PH), particularly those with elevated diastolic pulmonary vascular pressure gradient (DPG) [3]. Of note, in the study by Fayyaz et al . [2], diagnosis of PH was solely based on echocardiography. Furthermore, in their study, DPG was 3 mmHg and pulmonary vascular resistance (PVR) was 3.9 WU in the subgroup of 30 patients with available invasive haemodynamic data, thus resembling the haemodynamic phenotype of Ipc-PH. Application of these data are therefore limited to Ipc-PH and cannot be applied to Cpc-PH. Haemodynamic estimates of pulmonary vascular disease are a major requirement for the understanding and management of patients with pulmonary hypertension due to left heart disease http://ow.ly/ABsl30nuXX2